Effect of binder type and other parameters in synthesis of magnesite chromite refractories from process waste - Kalpakli, YK; Gökmen, S; Özgen, S (ELSEVIER SCI LTD, 2002)
Recycling of the process waste in basic refractory production will not only make it possible to put the waste substances to use but also help to solve the problems of environmental pollution and storing. This paper is the first part of a study on using the magnesite and chromite dusts in refractory production, accumulated in -10(-3) m and finer particle fraction as process waste at the Konya Chrome-Magnesite Plant. In this work, three different MgO and Cr2O3 compositions were studied. Magnesite ore is added to the mixture without any thermal process. The type and proportion of the bond to be used, particle size distribution of the magnesite and chromite ores and the influence of compaction pressure on the refractory properties were examined. Consequently the influence of the changes in the mixture composition and sintering temperature on refractory properties was studied. The results of the experiments revealed the optimum type and content of the bond as MgSO(4)(.)7H(2)O and 8%, and optimum pressing pressure of the materials containing raw magnesite at 250 MPa. It was observed that when the chromite content of the material composition increased from 10 to 28% and 50%, the cold crushing strength (CCS) of the material has decreased, yet its porosity (P%) increased. This improves when the sintering temperature increased from 1450 to 1550 degreesC and 1750 degreesC. The optimum sintering temperature was found at 1750 degreesC. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: refractories; MgO; Cr2O3; sintering; mechanical properties; basic refractories; Materials Science